2010
DOI: 10.1007/s00280-010-1311-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of S-1 in patients with gemcitabine-resistant advanced pancreatic cancer

Abstract: Second-line chemotherapy with S-1 was tolerated with acceptable toxicity and resulted in a relatively high disease control rate in patients with gemcitabine-resistant advanced pancreatic cancer. As an oral agent, S-1 may be a feasible treatment option for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 18 publications
3
34
1
Order By: Relevance
“…In our study, the median OS of the two groups was 4.5 and 4.4 months with no statistical significance. These numbers were close to the results in two phase II studies [14,15] of S-1 monotherapy as second-line chemotherapy for advanced pancreatic cancer after gemcitabine failure (median survival time 4.5-6.3 months). The RR was disappointing as only 1 patient in the daily group showed PR with no CR/PR in the alternate-day group.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, the median OS of the two groups was 4.5 and 4.4 months with no statistical significance. These numbers were close to the results in two phase II studies [14,15] of S-1 monotherapy as second-line chemotherapy for advanced pancreatic cancer after gemcitabine failure (median survival time 4.5-6.3 months). The RR was disappointing as only 1 patient in the daily group showed PR with no CR/PR in the alternate-day group.…”
Section: Discussionsupporting
confidence: 64%
“…Differentiating between the relative roles of gemcitabine and S-1 in overcoming tumor resistance is difficult. The efficacy and survival data obtained in the present study seem to be better than those of previous studies for oral fluoropyrimidine monotherapy as a salvage chemotherapy for advanced pancreatic carcinoma (Table 6) [1,2,17,28,29]. However, since all the data were obtained in single-arm studies, a randomized study is needed to make these suggestions reliable.…”
Section: Discussioncontrasting
confidence: 57%
“…In gemcitabine-refractory metastatic pancreatic cancer, our recent phase II study of S-1 yielded results that demonstrated marginal activity including a response rate of 15%, a median progression-free survival time of 2.0 months and a median overall survival time of 4.5 months, with a favorable toxicity profile [17]. In addition, other reports also demonstrated marginal antitumor activity [1,28]. Gemcitabine administration via infusion at a fixed dose rate of 10 mg/m 2 /min (FDR-Gem) has been found to increase the intracellular drug concentrations, compared with gemcitabine at a standard dose rate infusion over a period of 30 min.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, several recent studies assessed S-1 monotherapy as second-line treatment for advanced pancreatic cancer after gemcitabine failure. Median progression-free survival was 2.0 to 4.1 months, and overall survival data 4.5 to 6.3 months, respectively [19][20][21]; thereby reaching survival data as reported in the initial first line gemcitabine trial by Burris and co-workers [2]. The authors concluded that S-1 as monotherapy had only marginal anti-tumour activity in patients with gemcitabine-refractory metastatic pancreatic cancer.…”
Section: Discussionmentioning
confidence: 81%